CULTIVATING CIVIC CHARACTER THROUGH CO-CURRICULAR PROGRAMS CONTAINING LOCAL WISDOM - Amelia Sholihah; Sudrajat (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of local wisdom-based co-curricular programs on the formation of student citizenship character at SMP Negeri 16 Cimahi. The co-curricular program implemented takes the theme